Understanding and managing type 2 diabetes - Baricevic, Thomas (Video Education Australasia, 2007)
This program has been developed as a response to growing demand for diabetic nursing knowledge, signs and symptoms awareness and management of type 2 diabetes. It will provide a learning resource for both nursing students and clinical nurses delivering hands-on nursing care.